The effect of solution focused therapy on reducing psychosocial problems in patients with substance use disorder: systematic review - Erkuş , Şeyma; Babaoğlu, Elçin (Journal of Dependence, 2025)
This systematic review aims to assess the impact of solution-focused therapy (SFT) on mitigating psychosocial issues among patients with substance use disorder. A comprehensive literature search was conducted using databases including PsycInfo, SpringerLink, Cochrane, PubMed, ProQuest, Science Direct, Networked Digital Library of Theses and Dissertations (NDLTD), and ULAKBIM. Articles published within the past decade in English were included, with search terms comprising “substance use disorder,” “solution-focused therapy,” and related combinations. After screening titles and abstracts, eight studies—four randomized controlled trials and four non-randomized studies—met the inclusion criteria and were included in the review. Findings suggest that SFT has a beneficial effect on reducing psychosocial challenges in substance use disorder patients. SFT demonstrated efficacy in alleviating symptom distress, interpersonal relationship issues, social role dysfunction, impulsivity, well-being deficits, and addiction-related symptoms. Additionally, it was found to support recovery processes, enhance self-efficacy, foster an internal locus of control, and reduce trauma and anxiety symptoms. SFT was administered in individual or group formats, with session durations ranging from 30 to 90 minutes, delivered either twice weekly or biweekly over 1 to 12 sessions. Subjective measures assessing psychosocial outcomes were predominantly used across studies to evaluate the impact of SFT. The review highlights the need for more randomized controlled trials to further validate the effectiveness of SFT in this population.